Antioxidant and antibacterial activity of Ipomoea mauritiana Jacq.: a traditionally used medicinal plant in Bangladesh - Alam, Istiak; Forid, Shaekh; Roney, Miah; Fadhlizil Fasihi, Mohd Aluwi (Springer Nature, 2020)
Background: In an attempt to explore the scientific basis for the pharmacological benefits the antioxidant and antimicrobial activities of Ipomoea mauritiana whole plant methanol extract were assessed.